Sport mega-event fantasies to financialization: the case of Porto Maravilha - Zainab Bhimani; Amanda De Lisio (Frontiers Media S.A., 2023)
This paper examines the relationship between sport mega-event construction and the financialization of housing in Rio de Janeiro. It focuses on the area of Porto Maravilha, constructed prior to the 2016 Olympic Games, and the particular use of the 2001 federal Statute of City and 1995 Strategic Plan for Rio de Janeiro to create new possibilities for neoliberal-capitalist expansion, initially disguised as democratized access to land yet, in effect, further commoditized land into a form of fictitious capital. To do so, we follow the work of Brazilian architect and author, Raquel Rolnik, and her argument that the legal-institutional emphasis on wealth distribution in urban legislation, propagated at the time of the internationally recognized sport mega-event in Brazil, was not adequately harnessed and instead used to endorse real estate speculation and uneven development in the metropolitan area. The coordination and collaboration between state and nonstate entities in mega-event construction is typically associated with deepened socio-spatial inequities, the privatization of public resource material, and the in/direct displacement of low-income communities. We review pertinent literature to better understand the role of sport mega-event fantasies in the construction of Porto Maravilha-which we come to understand as a speculative logic lubricant for finance. We do this to call attention to future studies to be particularly attuned to financialization in mega-event cities.